Harnessing DLL3 inhibition: From old promises to new therapeutic horizons - Cortinovis, Diego Luigi; Colonese, Francesca; Abbate, Maria Ida; Sala, Luca; Meazza Prina, Marco; Cordani, Nicoletta; Sala, Elisa; Canova, Stefania (Frontiers in Medicine, 2022)
Small-cell lung cancer (SCLC) is an aggressive neuroendocrine tumor with a high relapse rate, limited therapeutic options, and poor prognosis. The combination of chemotherapy and immune-checkpoint inhibitors brings a new therapeutic era, although the lack of predictive biomarkers of response reduces the efficacy of applying the treatment to the entire population of patients with SCLC. The lack of treatments able to bind to a specific target has always been a substantial difference to the non-small cell lung cancer (NSCLC) counterpart. Delta-like canonical Notch ligand 3 is a protein frequently overexpressed in SCLC and is therefore being explored as a potentially promising therapeutic target in high-grade neuroendocrine lung cancer. In this article, we critically review the activity and efficacy of old DLL3 inhibitors antibody-drug conjugate (ADC) and their failures through new compounds and their possible applications in clinical practice, with a focus on new molecular classification of SCLC.